Hygienic conditions of minimally-processed watercress, lettuce and cabbage, and fresh-cut lettuce - Rapanello, Evelyn (2009)
With the purpose of assessing the hygienic conditions of package ready-to-eat vegetables sold in the ABC region- SP, 20 samples of each type of minimally-processed vegetables, watercress, lettuce and cabbage were analyzed, in addition to 25 fresh-cut lettuce samples. Coliforms and Escherichia coli were analyzed by means of the most probable number (MPN) technique, and Salmonella, Listeria monocytogenes and Yersinia enterocolitica by the conventional culture technique. Centrifugal-flotation technique was carried out for enteroparasites detection. Fecal coliforms MNP values higher than 102/g were observed in 60.0% of cabbage, 50.0% of watercress, and 20.0% of lettuce minimally-processed samples. In 48.0% of fresh-cut lettuce samples, the MPN values of fecal coliforms was higher than 2x102/g. Escherichia coli was evidenced in 45.0%, 30.0% and 20.0% of watercress, cabbage and fresh-cut lettuce samples, respectively. Salmonella was isolated from 5.0% and 4.0% of watercress and fresh-cut lettuce samples, respectively, and Yersinia enterocolitica was found on 5.0% of cabbage samples. Enteroparasites were detected on 7.1% of watercress and on 20.0% of fresh-cut lettuce samples. Good manufacturing practices implementation on whole vegetable-produce chain is relevant, in order to assure the availability of safe products to population.